Profile of the \(^{12}\)CO(3-2) Emission Line Detected From the Debris Disc of 49 Ceti - Tuyet Nhung, Pham Thi; Anh, Pham Tuan; Hoai, Do Thi; Diep, Pham Ngoc; Phuong, Nguyen Thi; Thao, Nguyen Thi; Dariulat, Pierre (Communications in Physics, 2017)
The CO(3-2) emission of the debris disc of the young A star 49 Ceti, known to be particularly gas rich, has been recently detected and measured using the ALMA interferometer. We study the observed line profile and comment on each of the possible contributions to its width. Line broadening is found to be dominated by Keplerian shear and an upper limit of 0.8 kms FWHM is placed on other possible contributions,including temperature, confirming the quietness of the gas contained in the disc and disfavouring models that would require relatively violent events to generate secondary gas.